Collegial Peer Coaching Model: A Case Study in Empowering Science Teachers - De La Cruz, Teresita V. (JPAIR Multidisciplinary Research, 2012)
This study was an attempt to develop and validate the proposed Collegial Peer Coaching Model (CPCM) for Science Teachers across various levels at Southern Luzon State University, Lucban, Quezon. The research design is a combination of descriptive-qualitative and developmental research methods involving 18 science teachers in the primary, secondary and tertiary levels. Three instruments were developed for the study - a teacher performance scale, a primer on peer coaching and an evaluation questionnaire. Results suggest that the participants had highly favorable performance ratings in the conduct of the three instructional components of the CPCM, as most participants achieved either ’very satisfactory’ or ’outstanding’ ratings after the conduct of the model, in comparison to their pre-CPCM ratings. The predominantly identified criteria for classroom observation are discussed as well as the quantity increases obtained by science teachers by group level along the three instructional components. The acceptability ratings also indicate very favorable scores. Among the conclusions made, it seems that the science teachers’ teaching science performance require more skills improvement and/or refinement in the component identified as the "management of the teaching-learning activities" than in "classroom management skills" and "personal qualities".